VANICLÉIA SILVA SANTOS: REFERENCE IN AFRICAN STUDIES IN BRAZIL - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Vanicléia was born August 25, 1977, in Jacobina-BA. He was the first person of the generation of his parents’ families to finish high school, there he realized that following the path of studies would open up many possibilities to give a better life to his family. Completed his graduation in 1998 at UNEB, did his master’s at (PUC / SP), a doctorate at the University of São Paulo and a postdoctoral degree at The University of Texas at Austin (2016). Since 2010, she is a professor and researcher at the Federal University of Minas Gerais. She is currently a graduate of UFMG and works as an Associate Curator of the African Art Collection at the Penn Museum of the University of Pennsylvania in the United States. Vanicléia is a great reference for all about the history of Africa.